Preparation of Village Revenue and Expenditure Budgets in The Jorong Sub-District of Tanah Laut District - Irawanto; Singgih Priono; Riky Welli Saputra (Asian Journal of Community Services, 2023)
The preparation of the Village Revenue and Expenditure Budget (APBDes) is a public document for villages in the next year. For this reason, the APBDes must be prepared properly by involving various stakeholders so that it will be reflected in relation to village revenues and expenditures, besides that the APBDes is a form of transparency in the implementation of development in the village. This socialization aims to provide insight and knowledge to village apparatus in preparing the APBDes in Jorong District, Tanah Laut Regency, South Kalimantan Province.